Proving the viability of an electrochemical process for the simultaneous extraction of oxygen and production of metal alloys from lunar regolith. (January 2020) - Lomax, Bethany A.; Conti, Melchiorre; Khan, Nader; Bennett, Nick S.; Ganin, Alexey Y.; Symes, Mark D.
Abstract: The development of an efficient process to simultaneously extract oxygen and metals from lunar regolith by way of in-situ resource utilisation (ISRU) has the potential to enable sustainable activities beyond Earth. The Metalysis-FFC (Fray, Farthing, Chen) process has recently been proven for the industrial-scale production of metals and alloys, leading to the present investigation into the potential application of this process to regolith-like materials. This paper provides a proof-of-concept for the electro-deoxidation of powdered solid-state lunar regolith simulant using an oxygen-evolving SnO2 anode, and constitutes the first in-depth study of regolith reduction by this process that fully characterises and quantifies both the anodic and cathodic products. Analysis of the resulting metallic powder shows that 96% of the total oxygen was successfully extracted to give a mixed metal alloy product. Approximately a third of the total oxygen in the sample was detected in the off-gas, with the remaining oxygen being lost to corrosion of the reactor vessel. We anticipate, with appropriate adjustments to the experimental set-up and operating parameters, to be able to isolate essentially all of the oxygen from lunar regolith simulants using this process, leading to the exciting possibility of concomitant oxygen generation and metal alloy production on the lunar surface. Graphical abstract: Image 1 Highlights: The electro-deoxidation of the lunar regolith simulant JSC-2A is demonstrated. The approach is based on the FFC-Cambridge process. 96% of the total oxygen can be extracted to give a metal alloy product. Roughly one third of the total oxygen in the sample was detected in the off-gas. The remaining oxygen is likely lost to corrosion of the reactor vessel.